Two-dimensional tension analysis of subsea cable using minimization without gradient based technique - Jasman, Nur Azira (2021)
Subsea telecommunication cable has been used extensively since the 1850’s and the deployment of subsea cable continues to be a risky and challenging operation encountered by engineers due to many uncertainties. Analysis of subsea cable tension is very important in the design stage, to ensure that the cables are laid out according to plan. A free hanging subsea cable that is connected from a floating vessel to the seabed, has been known to be the most common configuration deployed near to platform. However, this conventional configuration produces a large hang-off load on the subsea cables which could potentially cause buckling issues at touchdown point. An alternative configuration is created by considering the use of buoyancy module attached to certain parts of the subsea cable in order to reduce stress and avoid failure. In this research, the formulation of mathematical model in steady state condition related to the free hanging subsea cable configuration is improved on obtaining the top tension by considering a single point moment at the top node based on the physical law of subsea cable. The linear element of subsea cable is introduced by discretizing the cable element on each region accordingly. The mathematical model for the conventional configuration is developed as the first step to improve the analysis of subsea cable tension problem and to provide an insight on the position of maximum tension produced on the cable. The mathematical model obtained is then extended for the configuration with buoyancy module attached to the subsea cable. Tension analysis for both subsea cable configurations, were solved using minimization without gradient-based technique. This technique produces results that converge to exact solution considering the implementation of additional assumption and condition on the formulated mathematical model. The conventional subsea cable configuration shows maximum tension at the hang-off section, a situation that causes extreme stress on the subsea cable. However, the new subsea cable configurations developed in this research have been shown to reduce the subsea cable tension, especially at the hang-off section. In conclusion, a single buoyancy module attached to specific position on the subsea cable could reduce the extreme stress of cable and prevent cable breaks.